Supply chain risk assessment - Þórhallur Jóhannsson 1977- (2015)
This thesis is intended to perform risk assessment of the supply chain focusing on maritime transports to and from Iceland. Companies that depend on secure and stable maritime transports need to be well informed and understand the risk of their supply chain disrupting. The assessment is performed by proposing research questions aimed at identifying key risk factors in the chain. Two techniques are selected that have different approach to identify risk factors. Firstly a so-called FMEA technique that approaches the assessment from bottom-up and secondly a so-called FTA technique that approaches the assessment from a top-down approach. The methodology of the techniques as well as the process of performing the techniques is described step by step in the thesis. The techniques provide in combination nine risk factors that are classified as key risk factors in addition to various other risk factors classified as less urgent.